Assessment of Agriculture Productivity Performance in the Tarai Region of Nepal - Dhakal, Bhola Nath (Economic Review of Nepal, 2024)
Improvement in agriculture is crucial for the food security of growing population. Land efficiency is enlightened by crop production in terms of yield per unit of land. Spatial assessment of agricultural productivity highlighted to explore the relation of the land structure and complexity on production through efficiency measurement of farmers. The present paper attempts to assess the spatial performance of agriculture productivity by the districts in the Tarai region of Nepal. The secondary data sources have been collected from Ministry of Agriculture and Livestock Development, Kathmandu for the period of 1967/68 to 2020/21. Composite Agriculture Productivity Index (CAPI) method has been adopted to identify the spatial performance. Yield of principal food crops (paddy, maize, wheat, millet and barley) and cultivated area has been used in the districts of Tarai region of Nepal to assess the spatial performance of agriculture productivity. The districts have been classified as High Productivity, Moderate Productivity and Low Productivity districts based on the productivity index of major crops. It is concluded that the scenario of agriculture productivity in Tarai during the study period is not encouraging. It is noticed that nearly 75 percent districts have been observed with low and moderate productivity. Among them, Nawalparasi, Sunsari, Jhapa, Rupandehi and Sarlahi districts have been found under high productivity districts. There has been no significant change in productivity during the study period.